dose - dependent protective effects of silymarin against ccU - induced liver damage in rats - AL-shAWI, nada Naji; Hussain, saad Abdel-Rehman; Ali, husam HASSON; Rashid, yahia Zeki; numan, Nawfal Abdel-munim (Journal of the Faculty of Medicine Baghdad, 2005)
Background: